Dictionary of Australian and New Guinean Mammals - Strahan, Ronald and Conder, Pamela (Collingwood CSIRO Publishers, 2007)
Here for the first time is a unified guide to the mammals of both Australia and Melanesia. Based on Ronald Strahan's first dictionary of Australian mammals, published in 1981, it includes all species, both native and introduced, extant and believed extinct.
Include Illustrations and Index
Keywords: Mammals